Predictive value of preoperative magnetic resonance imaging structural and diffusion indices for the results of trigeminal neuralgia microvascular decompression surgery. - Zhang, Yang; Sun, Dengbin; Xie, Yunjie; Li, Rui; Zhao, Hang; Wang, Zhaoping; Feng, Lei (Neuroradiology, 2023)
Purpose: To explore the predictive value of preoperative magnetic resonance imaging structural and diffusion indices of the spinal trigeminal tract (SpTV) on the results of microvascular decompression (MVD) in patients with trigeminal neuralgia (TN). Methods: This retrospective study included patients diagnosed with TN and treated with MVD in the Jining First People's Hospital between January 2020 and January 2021. The patients were divided into good and poor results groups according to postoperative pain relief. Logistic regression analysis was performed to explore independent risk factors for poor results of MVD, and their predictive value was examined using receiver operating characteristic (ROC) curves. Results: A total of 97 TN cases were included, 24 cases with a poor result and 73 with a good result. They were comparable in demographic characteristics. Fractional anisotropy (FA) was lower (P < 0.001), and radial diffusivity (RD) was higher (P < 0.001) in the poor result group compared to the good result group. Patients in the good result group showed a higher proportion of grade 3 neurovascular contact (NVC) (39.7% vs. 16.7%, P = 0.001) and a lower RD (P < 0.001). The multivariate analysis showed that the RD of SpTV (OR = 0.000016, 95% CI: 0.000–0.004, P < 0.001) and NVC (OR = 8.07, 95% CI: 1.67–38.93, P = 0.009) were independently associated with poor results. The area under the curve (AUC) of RD and NVC were 0.848 and 0.710, and their combination achieved an AUC of 0.880. Conclusion: NVC and RD of SpTV are independent risk factors for poor results after MVD surgery, and combining the NVC and RD might achieve relatively high predictive value for poor results.